2015
DOI: 10.1038/nprot.2015.125
|View full text |Cite
|
Sign up to set email alerts
|

Sample preparation for high-resolution 3D confocal imaging of mouse skeletal tissue

Abstract: High-resolution confocal imaging is a vital tool for analyzing the 3D architecture and detailed spatial distribution of cells in situ. However, imaging of skeletal tissue has remained technically challenging because of its calcified nature. Here we describe a protocol that allows high-resolution imaging of skeletal tissue with preservation of cellular morphology and tissue architecture. The procedure involves tissue fixation, decalcification and cryosectioning of the mouse skeletal tissue to generate thick sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(125 citation statements)
references
References 33 publications
2
123
0
Order By: Relevance
“…The bones were then incubated in 20% sucrose and 2% polyvinylpyrrolidone (PVP) solution for 24 h, as described previously333435. Finally, we embedded the tissues in 8% gelatin (porcine; Sigma, G2500) in presence of 20% sucrose and 2% PVP (Sigma, PVP360).…”
Section: Methodsmentioning
confidence: 99%
“…The bones were then incubated in 20% sucrose and 2% polyvinylpyrrolidone (PVP) solution for 24 h, as described previously333435. Finally, we embedded the tissues in 8% gelatin (porcine; Sigma, G2500) in presence of 20% sucrose and 2% PVP (Sigma, PVP360).…”
Section: Methodsmentioning
confidence: 99%
“…Such early studies also suggested that the organization of the bone vasculature is similar in different mammalian species, including rats, rabbits, guinea pigs and humans (Trueta and Morgan, 1960). In recent years, various technological advancements, such as the identification of cell type-specific markers, transgenic florescent reporters, imaging by confocal and two-photon microscopy, microcomputed tomography (micro-CT), three-dimensional (3D) reconstruction of imaging data, and improved protocols for tissue processing and immunostaining, have advanced our understanding of the organization of the bone vasculature and its functional specialization (Acar et al, 2015;Kunisaki et al, 2013;Kusumbe et al, 2014Kusumbe et al, , 2015Roche et al, 2012).…”
Section: Architecture Of the Bone Vasculaturementioning
confidence: 99%
“…The comprehensive methodology from collecting fresh bone tissues to cryosectioning and immunostaining has been described previously. 28 Imaging bone samples with confocal/two-photon microscopy Basic microscope settings. The bone structure can be visualised by SHG using a Chameleon laser at 900 nm (Coherent, Santa Clara, CA, USA), while Vybrant-DiD labelled cancer cells can be visualised using a 633 nm HeNe laser and Vybrant DiI/CM-DiI with a 543 nm HeNe laser.…”
Section: Frozen Bone Sample Preparationmentioning
confidence: 99%